2010
DOI: 10.1104/pp.110.154740
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nucleocytoplasmic Shuttling of an Arabidopsis SR Splicing Factor: Role of the RNA-Binding Domains      

Abstract: Serine/arginine-rich (SR) proteins are essential nuclear-localized splicing factors. We have investigated the dynamic subcellular distribution of the Arabidopsis (Arabidopsis thaliana) RSZp22 protein, a homolog of the human 9G8 SR factor. Little is known about the determinants underlying the control of plant SR protein dynamics, and so far most studies relied on ectopic transient overexpression. Here, we provide a detailed analysis of the RSZp22 expression profile and describe its nucleocytoplasmic shuttling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 69 publications
(108 reference statements)
2
70
0
Order By: Relevance
“…AtRSZ22-GFP was shown to concentrate in the nucleolus upon phosphorylation inhibition, while other tested AtSRs did not (Tillemans et al, 2006). Later studies in root and pollen cells of stably transformed plants confirmed the accumulation of AtRSZ22-GFP within nucleoli upon phosphorylation inhibition (Rausin et al, 2010). In transiently expressing root cells, AtRS31-GFP, unlike other tested SRs, accumulated into concave cap-like structures surrounding regions devoid of fluorescence corresponding to the nucleoli following treatment with staurosporine.…”
Section: Phosphorylation and Dephosphorylationmentioning
confidence: 71%
See 3 more Smart Citations
“…AtRSZ22-GFP was shown to concentrate in the nucleolus upon phosphorylation inhibition, while other tested AtSRs did not (Tillemans et al, 2006). Later studies in root and pollen cells of stably transformed plants confirmed the accumulation of AtRSZ22-GFP within nucleoli upon phosphorylation inhibition (Rausin et al, 2010). In transiently expressing root cells, AtRS31-GFP, unlike other tested SRs, accumulated into concave cap-like structures surrounding regions devoid of fluorescence corresponding to the nucleoli following treatment with staurosporine.…”
Section: Phosphorylation and Dephosphorylationmentioning
confidence: 71%
“…A sensitive shuttling assay using FLIP and nuclear export inhibitors with cells transiently expressing FP fusions strongly suggested that RSZ22 is a nucleocytoplasmic shuttling SR splicing factor (Tillemans et al, 2006). The dynamics of RSZ22 was recently studied in stable transformants enabling tissue-specific expression of the transgene (Rausin et al, 2010). The results demonstrated that RSZ22 is a bona fide nucleocytoplasmic shuttling SR protein.…”
Section: Dynamics Of Splicing Regulatorsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, dehydration stress and heat stress increase the production of transcripts encoding the full-length SR45a protein, an atypical SR-like protein, relative to other splice variants (Gulledge et al, 2012). Furthermore, stress signals affect both the phosphorylation status and subcellular localization of Arabidopsis SR and splicingrelated proteins (Ali et al, 2003;Tillemans et al, 2005Tillemans et al, , 2006de la Fuente van Bentem et al, 2008;Koroleva et al, 2009;Rausin et al, 2010). Phosphorylation may affect the function of SF protein isoforms.…”
Section: As Of Sfs In Response To Abiotic Stressmentioning
confidence: 99%